Cryptic Lineage and Genetic Structure of Acanthopagrus pacificus Populations in a Natural World Heritage Site Revealed by Population Genetic Analysis - Islam, Md Rakeb-Ul; Tachihara, Katsunori; Imai, Hideyuki (Diversity, 2022)
Recent studies have revealed extensive genetic differentiation among some populations of marine taxa that were previously believed to be essentially homogeneous because larvae are widely dispersed in ocean currents. Acanthopagrus pacificus is a commercially and ecologically important teleost fish that is endemic to shallow coastal waters and estuaries of some tropical and sub-tropical areas in the West Pacific Ocean. Here, we examined genetic structure and the inferred demographic history of A. pacificus populations from mtDNA control region sequence data. A 677–678 base-pair fragment was sequenced from 159 individuals sampled at three localities across the West Pacific Ocean. Haplotype diversity was high, ranging from 0.915 to 0.989, while nucleotide diversity was low to medium, ranging from 0.8% to 2.60%. Analysis of molecular variance (AMOVA) showed significant genetic subdivision (FST = 0.155, p < 0.05) among sampled populations while pairwise FST estimates also revealed strong genetic differentiation among populations indicating that gene flow was restricted. Two distinct cryptic lineages were identified that were estimated to have diverged during the Pleistocene. In summary, contemporary factors including regional oceanic currents and self-recruitment are considered to have played significant roles in producing the population structure in this fish. In particular, the genetic information generated in the current study will allow appropriate fisheries management and conservation strategies to be developed for this important local fish in the waters around Iriomotejima Island, a World Heritage site.